"Becoming the man you always wanted to be": Exploring the representation of health and masculinity in Men's Health magazine. (15th October 2018) - Lewington, Lily; Sebar, Bernadette; Lee, Jessica
Abstract: Issue addressed: Men's health and lifestyle magazines are a popular medium through which hegemonic ideals of masculinity are displayed, influencing the way men behave and think about health (Crawshaw, 2007, Soc Sci Med, 65, 1606; Stibbe, 2004, Men Masc, 7, 31). Methods: This study conducted a critical discourse analysis of Australia's most popular men's health and lifestyle magazine, Men's Health, in order to understand how health is presented to men. Six issues were examined, from April 2016 to September 2016. Results: Three themes supporting hegemonic masculine discourses were revealed: a forged physique, (hetero)sexual prowess and career dominance. A fourth theme, the new man, was also identified revealing a shift in attitudes towards nutrition and style. Conclusions: Despite this shift in the representation of masculinity, hegemonic ideals remain dominant in the construction of Australian masculinity in this popular men's health and lifestyle magazine. So what?: This study highlights the utility of Men's Health magazine in promoting health and brings into question whether the current representation of masculinity works towards improving or decreasing the health of Australian men.